2022
DOI: 10.1039/d1sc04122c
|View full text |Cite
|
Sign up to set email alerts
|

Free-standing 2D non-van der Waals antiferromagnetic hexagonal FeSe semiconductor: halide-assisted chemical synthesis and Fe2+ related magnetic transitions

Abstract: The scarcity of two-dimensional (2D) magnetic nanostructures has hindered their applications in spintronics, which is attributed to that most magnetic materials exhibit non-van der Waals (nvdWs) structure and it is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…18,49 With Fe intercalation in NbSe 2 , a new peak appears at 251.9 cm −1 for the Fe 0.14 NbSe 2 crystal, which corresponds to the Fe− Se stretching vibration mode. 50 Further increase in Fe intercalation (Fe 0.225 NbSe 2 ) resulted in the shifting of the Fe− Se vibration mode to a higher frequency, which may be attributed to the ordering of Fe atoms in the 2H(I) superstructure. Finally, with more increase in Fe intercalation (Fe 0.38 NbSe 2 ) resulted in broad peaks.…”
Section: ■ Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…18,49 With Fe intercalation in NbSe 2 , a new peak appears at 251.9 cm −1 for the Fe 0.14 NbSe 2 crystal, which corresponds to the Fe− Se stretching vibration mode. 50 Further increase in Fe intercalation (Fe 0.225 NbSe 2 ) resulted in the shifting of the Fe− Se vibration mode to a higher frequency, which may be attributed to the ordering of Fe atoms in the 2H(I) superstructure. Finally, with more increase in Fe intercalation (Fe 0.38 NbSe 2 ) resulted in broad peaks.…”
Section: ■ Introductionsupporting
confidence: 86%
“…Further, to observe the structural changes upon intercalation, Raman spectroscopy study was carried out on selected single crystals of Fe x NbSe 2 ( x = 0, 0.14, 0.225, and 0.38) as shown in Figure . In pristine 2H-NbSe 2 , peaks observed at ∼230 and 240.5 cm –1 correspond to out-of-plane A 1g and in-plane E 2g phonon modes, respectively. , With Fe intercalation in NbSe 2 , a new peak appears at 251.9 cm –1 for the Fe 0.14 NbSe 2 crystal, which corresponds to the Fe–Se stretching vibration mode . Further increase in Fe intercalation (Fe 0.225 NbSe 2 ) resulted in the shifting of the Fe–Se vibration mode to a higher frequency, which may be attributed to the ordering of Fe atoms in the 2H­(I) superstructure.…”
Section: Resultsmentioning
confidence: 81%
“…[ 37 ] reported that trigonal ultrathin Cr 2 Te 3 films are FM with T C = 195 K and exhibit strong perpendicular magnetic anisotropy with 5 × 10 6 J m −3 , and Li et al [ 38 ] prepared 2D nanosheets of α‐MnSe 2 with nonstoichiometric surfaces via soft chemical etching, which were found to be a FM semiconductor with T C = 320 K. In addition, the robust FM/AFM order have also been found in 2D non‐vdW CrSe 2 , Fe 7 Se 8 , Cr 5 Te 8 , FeTe, CrTe, α‐MnSe 2 , and FeSe ultrathin films, their T C is up to 110, 300, 160, 220, 367, 160, and 553 K, respectively. [ 27,28,31,38–41 ] Compared to 2D vdW magnets, 2D non‐vdW ultrathin films have strong interlayer chemical bonding. Intuitively, the Curie temperature in the 2D non‐vdW magnetic materials could be significantly elevated by the enhanced interlayer magnetic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Moreover, the 2D hexagonal AFM semiconductor FeSe with few unit‐cell thicknesses are also quite stable, and it could remain without phase transformation after exposure to air for a month or being heat treated at 600 K for 1 h under a N 2 atmosphere. [ 41 ]…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Fe-based chalcogenides have received significant attention due to the intriguing discoveries of superconductivity and magnetism. Fe 7 Se 8 was demonstrated to be ferrimagnetic with a high Néel temperature of 455 K, showing great application prospects in the field of RT spintronic devices. In addition, Fe 7 Se 8 is one of the few systems possessing spin reorientation (the easy axis changes from the c -plane toward the c -axis at about 130 K), which is expected to have a large magnetocaloric effect in a wide temperature range .…”
mentioning
confidence: 99%